Modelling the Impact of Direct and Indirect Taxes Using Complementary Datasets - Michael Savage; Tim Callan (Institute for the Study of Labor (IZA), 2015)
Comprehensive modelling of the impact of taxes and tax policy options requires data on the impact at micro-level of both direct and indirect taxes. There are, however, limits on the amount of data that can be gathered by any one survey. With some exceptions, most notably the Living Costs and Food Survey (LCF) in the UK, most national expenditure surveys are not suitable for use in detailed modelling of the direct tax and welfare system. This makes approaches which impute expenditure data into detailed income surveys of considerable interest. In this paper, we assess the sensitivity of the distributional effects of indirect taxes to the choice between actual, estimated and imputed expenditure data. By doing so, the analysis here serves as an updated picture of the distributional effects of the indirect tax system in Ireland, as well as a base for future microsimulation analysis of simultaneous direct tax, indirect tax and welfare reform.
Keywords: D30; H22; H23; H24; 330; indirect tax; imputation; distribution; microsimulation